2015
DOI: 10.1017/s0007114514004206
|View full text |Cite
|
Sign up to set email alerts
|

Dietarytrans-10,cis-12-conjugated linoleic acid alters fatty acid metabolism and microbiota composition in mice

Abstract: The main aim of the present study was to investigate the effects of dietary trans-10, cis-12-conjugated linoleic acid (t10c12-CLA) on intestinal microbiota composition and SCFA production. C57BL/6 mice (n 8 per group) were fed a standard diet either supplemented with t10c12-CLA (0·5 %, w/w) (intervention) or with no supplementation (control), daily for 8 weeks. Metabolic markers (serum glucose, leptin, insulin and TAG, and liver TAG) were assessed by ELISA commercial kits, tissue long-chain fatty acids and cae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 63 publications
2
63
0
2
Order By: Relevance
“…Based on the findings here, the progression toward NEC may be detected between 1–2 weeks prior to current clinical diagnosis, which is consistent with the previous data [22]. Such findings require validation in large multicentre studies, but the finding that 4/5 metabolites most associated with NEC were involved in linoleate metabolism is intriguing given that trans -10, cis -12-conjugated linoleic acid ( t 10 c 12-CLA) negatively impacts on lipid metabolism, mediated by alterations in gut microbiome [23]. As more metabolomic investigations are performed, the mechanism of linoleate metabolism in an inflammatory-mediated damage may be better elucidated, but the results of this study support the concept that it is, at least in part, mediated by the microbiome.…”
Section: Discussionsupporting
confidence: 85%
“…Based on the findings here, the progression toward NEC may be detected between 1–2 weeks prior to current clinical diagnosis, which is consistent with the previous data [22]. Such findings require validation in large multicentre studies, but the finding that 4/5 metabolites most associated with NEC were involved in linoleate metabolism is intriguing given that trans -10, cis -12-conjugated linoleic acid ( t 10 c 12-CLA) negatively impacts on lipid metabolism, mediated by alterations in gut microbiome [23]. As more metabolomic investigations are performed, the mechanism of linoleate metabolism in an inflammatory-mediated damage may be better elucidated, but the results of this study support the concept that it is, at least in part, mediated by the microbiome.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, despite a decrease in Bifidobacteria relative abundance after the low FODMAP diet, Actinobacteria richness and diversity was still higher in these patients in comparison to those on the high FODMAP diet. However, we also observed that the shift caused by the low FODMAP diet to the microbial community left a niche open to potentially harmful bacteria, such as Porphyromonadaceae,42 43 which we found to be strongly associated with urinary histamine levels.…”
Section: Discussionmentioning
confidence: 64%
“…The study was expanded to additional time points before and after the onset of NEC and they detected a temporal profile of these metabolites that were significantly different in infants with NEC versus controls. These findings are particularly intriguing, in light of a previous report that showed changes in the gut microbiome of mice after they were exposed to dietary trans-10, cis-12-conjugated linoleic acid (69). A new approach utilized existing metabolomic data from newborn screening and identified multiple acylcarnitines that differed significantly in preterm infants who subsequently developed NEC (70).…”
Section: Proteomics and Metabolomics Applied To Necmentioning
confidence: 88%